Protection of cats against feline leukemia virus by vaccination with a canarypox virus recombinant, ALVAC-FL. - Tartaglia, J (1993)
Two ALVAC (canarypox virus)-based recombinant viruses expressing the feline leukemia virus (FeLV) subgroup A env and gag genes were assessed for their protective efficacy in cats. Both recombinant viruses contained the entire gag gene. ALVAC-FL also expressed the entire envelope glycoprotein, while ALVAC-FL(dl IS) expressed an env-specific gene product deleted of the putative immunosuppressive region. Although only 50% of the cats vaccinated with ALVAC-FL(dl IS) were protected against persistent viremia after oronasal exposure to a homologous FeLV isolate, all cats administered ALVAC-FL resisted the challenge exposure. Significantly, protection was afforded in the absence of detectable FeLV-neutralizing antibodies. These results represent the first effective vaccination of cats against FeLV with a poxvirus-based recombinant vector and have implications that are relevant not only to FeLV vaccine development but also to developing vaccines against other retroviruses, including human immunodeficiency virus.